PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR - Lega Marisa; Sumadi Sumadi; Edy Haryono (JPG (Jurnal Penelitian Geografi), 2016)
This research was aimed to find out (1) The difference between students' study result that used cooperative learning model of make a match type and students' study result that used conventional learning model, (2) The effect of using cooperative learning model activities of make a match type on the students' learning achievement. This research used quasi experiment method. The populations of this research were the students of class VII 3 and class VII 4. Analysis data techniques that used in this research were t-test and analysis of simple linear regresion. The result showed (1) There was a difference between students' study result that used cooperative learning model of make a match type and students' result study that used conventional learning model, (2) There was an effect of using cooperative learning model activities of make a match type on the students' learning achievement.Penelitian ini bertujuan untuk mengetahui (1) perbedaan hasil belajar siswa yang menggunakan model pembelajaran kooperatif tipe make a match dengan hasil belajar yang menggunakan model pembelajaran konvensional, (2) pengaruh aktivitas penggunaan model pembelajaran kooperatif tipe make a match terhadap hasil belajar siswa. Penelitian menggunakan metode eskperimen semu. Populasi dalam penelitian ini adalah siswa kelas VII 3 dan kelas VII 4. Teknik analisis data yang digunakan adalah uji t dan analisis regresi linier sederhana. Hasil penelitian (1) ada perbedaan hasil belajar menggunakan model pembelajaran kooperatif tipe make a match dengan hasil belajar siswa yang menggunakan model pembelajaran konvensional, (2) ada pengaruh aktivitas penggunaan model pembelajaran kooperatif tipe make a match terhadap hasil belajar siswa.Kata kunci:pembelajaran kooperatif, model make a match, hasil belajar ips geografi